HISTORY OF STUDYING OF CyperaceaeJuss IN CISCAUCASIA - Natalia Gennad’evna Likhovid; Valentina Valentinovna Volkova (Вестник Северо-Кавказского федерального университета, 2022)
Studing of the family Cyperaceae Juss of Ciscaucasia can be divided onon the importance unpublished works. The first academic research of Ciscaucasiahad fragmentary character.With the release of Crimea-Caucasus flora F.M. Biberstein begins a detailed study of the family Cyperaceae Juss. on the ante. At the beginning of XX century, there are numerous studies on the flora of certain regions. At the present stage continues the study of Cyperaceae Juss.